Strong interfacial interactions of ZnS/Cu-TCPP hybrids contribute to excellent nonlinear optical absorption. (December 2022) - Liang, Yuning; Yuan, Xue; Zeng, Zaiping; Zhu, Baohua; Gu, Yuzong
Abstract: In recent years, the research and development of optoelectronic devices based on metal-organic frameworks (MOFs) have increasingly triggered the interest and attention of researchers. However, their nonlinear optical (NLO) properties are in urgent need of improvement. Herein, we first report a method to improve the NLO response of MOFs by decorating ZnS nanoparticles. The NLO response of the hybrid is found to be much higher than that of pure MOFs and ZnS by the Z-scan technique. At higher incident intensities, the hybrids exhibit a giant optical limiting (OL) response with OL threshold as low as 2.82 × 10 −7  J/cm 2, which is better than almost all organic and inorganic materials reported in the literature so far, demonstrating the great value of hybrids for OL devices. As revealed by XPS characterizations, transient absorption (TA) spectroscopy, and DFT calculations, the strong interfacial interaction between ZnS nanodots and Cu-TCPP nanosheets can effectively promote the charge transfer process between them and significantly inhibit the recombination of photogenerated charge carriers, thus achieving a substantial enhancement of the NLO response. The simple preparation method and extremely low OL threshold suggest that this MOF-based hybrids have great potential for application in OL photonic devices. Graphical abstract: Image 1 Highlights: Synthesis of ZnS/Cu-TCPP by one-step hydrothermal method for the first time. The OL threshold of ZnS/Cu-TCPP is better than all OL materials reported in the literature. The strong interfacial interaction leads to substantial enhancement of NLO response.